W.F. Stringer collection of strips of negatives and transparencies - Stringer, Walter, 1907-2001. (1940)
A collection of negatives and transparencies, in strips of various length, contained in 22 albums. Featuring works performed by all major resident Australia dance companies and all major overseas dance companies visiting Australia from the 1940s to the 1990s. Australian companies include the Australian Ballet, Borovanksy Ballet, National Theatre Ballet, the Ballet Guild, Dance Company (NSW), the West Australian Ballet and Sydney Dance Company. Visiting companies include the Alvin Ailey American Dance Theatre, Bolshoi Ballet, Georgian State Dance Company, Nederlands Dans Theatre, New York City Ballet, the Royal Winnipeg Ballet, Ballet Rambert and the Kirov Ballet. Material relating to the Australian Ballet is the most comprehensive part of the collection and all major productions by and leading dancers of the Australian Ballet are represented. Some of the major Australian artists represented are Robert Helpmann, Marilyn Jones, Garth Welch, Marilyn Rowe, Kelvin Coe, Kathleen Gorham, Graeme Murphy, Janet Vernon, Lucette Aldous and Gary Norman. There are also many slides showing the activities of back stage personnel and dancers with dramatic facial make-up.
Part of the W.F. Stringer collection.
Keywords: Australian Ballet -- Performances -- Photographs; Ballet dancers -- Australia -- Photographs; Ballerinas -- Australia -- Portraits; Ballet -- Australia -- Photographs; Dancers -- Australia -- Photographs; Dance -- Photographs; Ballet dancers; Dancers; Choreographers